2015
DOI: 10.3390/rs70404048
|View full text |Cite
|
Sign up to set email alerts
|

What Four Decades of Earth Observation Tell Us about Land Degradation in the Sahel?

Abstract: Abstract:The assessment of land degradation and the quantification of its effects on land productivity have been both a scientific and political challenge. After four decades of Earth Observation (EO) applications, little agreement has been gained on the magnitude and direction of land degradation in the Sahel. The large number of EO datasets and methods associated with the complex interactions among biophysical and social drivers of ecosystem changes make it difficult to apply aggregated EO indices for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 73 publications
3
67
0
Order By: Relevance
“…Changes in tree cover attributes (e.g., canopy cover and tree density) have primarily been analysed using high or medium resolution RS data in order to separate trees and shrubs from the herbaceous vegetation that dominate the RS signal during the growing season. However, recent research by Horion et al (2014) and has shown that coarse resolution NDVI data acquired during the dry season is an interesting alternative for analysing tree cover changes over larger spatial extents (Brandt et al 2015). …”
Section: Research Topicmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in tree cover attributes (e.g., canopy cover and tree density) have primarily been analysed using high or medium resolution RS data in order to separate trees and shrubs from the herbaceous vegetation that dominate the RS signal during the growing season. However, recent research by Horion et al (2014) and has shown that coarse resolution NDVI data acquired during the dry season is an interesting alternative for analysing tree cover changes over larger spatial extents (Brandt et al 2015). …”
Section: Research Topicmentioning
confidence: 99%
“…The second most common variable for vegetation change analysis in the SSZ is vegetation productivity derived from time series of coarse resolution RS data (e.g., AVHRR). Knauer et al (2014) and Mbow et al (2015) provide detailed descriptions of the many different approaches have been used to detect changes in vegetation productivity using coarse resolution RS data in the SSZ. Considerably less research has analysed changes in tree cover attributes and vegetation phenology using RS data.…”
Section: Research Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium to low spatial resolution remote sensing data (250 m -4 km pixel size) enable the detection of trends and anomalies of remotesensing derived indices or biophysical variables over large areas. Applications in the Sahel include studies on the dynamics of vegetation, land use, and land degradation (Dardel et al, 2014;Brandt et al, 2014a;Horion et al, 2014;Mbow et al, 2015), water bodies and wetlands (Moser et al, 2014) and precipitation (Nicholson, 2005). Yet, such data is insufficient to elucidate more specific social-land use practices (Turner, 2003), for which the use of high to very high spatial resolution data is required (Elmqvist and Khatir, 2007;Brandt et al, 2014b).…”
Section: Using Geospatial Analysis In a Contested Landscapementioning
confidence: 99%
“…Much of these investigations have aimed to refine methodological issues in order to accurately track land degradation in vulnerable areas, reduce uncertainties and explain inconsistencies among studies. For instance, a wide array of satellite-derived data, such as vegetation indices, normalized surface reflectance, brightness temperature or biomass net primary production derivatives (Mbow et al, 2015), have been utilized to appraise desertification effects in the Sahel (Mbow et al, 2015;Fensholt et al, 2013) and also in other African countries such as Kenya (Omuto, 2011), Somalia (Omuto et al, 2010), South Africa (Thompson et al, 2009) or Zimbabwe (Prince et al, 2009). Likewise, desertification in the Mediterranean region has been studied through satellite imagery in Greece (Bajocco et al, 2012), Israel (Shoshany and Karnibad, 2015) and the Iberian Peninsula (del Barrio et al, 2010).…”
mentioning
confidence: 99%